2022
DOI: 10.3389/fpsyg.2021.823123
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Functions of Playfulness in Adult English as a Foreign Language Learners: An Exploratory Study

Abstract: Influenced by the flowering of positive psychology in the field of foreign language acquisition research in recent years, the present study aimed to explore the perceived functions of playfulness, as a personality construct, among English as a foreign language (EFL) learners. To this aim, an initial sample of 38 EFL learners were selected randomly from the private language institutes of Mashhad, the second largest city in Iran. They were interviewed about any perceived functions of playfulness in the EFL learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, given the feedback sensitive nature of dynamic systems, language teachers can nurture moments of high enjoyment for their learners through emotional scaffolding, building rapport, and group work in which they can feel a sense of belonging, enthusiasm, and connectedness (Dewaele and Li, 2020 ). Furthermore, enhancing playfulness among learners can enable language learners to shift from feeling negative emotions to positive ones, such as enjoyment (Barabadi et al, 2022 ). One type of playfulness is other-directed playfulness which can pave the way for positive peer enjoyment contagion, as a result, learners might experience more enjoyment in the classroom (Shao and Parkinson, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, given the feedback sensitive nature of dynamic systems, language teachers can nurture moments of high enjoyment for their learners through emotional scaffolding, building rapport, and group work in which they can feel a sense of belonging, enthusiasm, and connectedness (Dewaele and Li, 2020 ). Furthermore, enhancing playfulness among learners can enable language learners to shift from feeling negative emotions to positive ones, such as enjoyment (Barabadi et al, 2022 ). One type of playfulness is other-directed playfulness which can pave the way for positive peer enjoyment contagion, as a result, learners might experience more enjoyment in the classroom (Shao and Parkinson, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to playfulness in the SLA domain, Barabadi et al (2022) investigated the playfulness among EFL learners within the context of Iran. The participants were interviewed about the perceived functions of FLP in their L2 learning.…”
Section: Foreign Language Playfulnessmentioning
confidence: 99%
“…This is because research findings show that individuals who enjoy a high level of playfulness recognize opportunities for leisure and may tend to experience less boredom in comparison to less playful counterparts (Barnett, 2012). Besides, greater playfulness in adults has been correlated with positive emotions and better emotion regulation (Barabadi et al, 2022) as well as the tendency to experience flow (Proyer, 2017). Thus, the present study is motivated by the assumption that more complete understanding of the complex, dynamic interplay of L2 emotions may improve pedagogical efforts and translate into better learning outcomes.…”
Section: The Link Between Flb Fle and Flpmentioning
confidence: 99%
“…Our aim was to expand the knowledge on how playfulness is reflected in language by asking participants to provide descriptions of what they understand as playfulness and using LIWC for text analysis. Prior research has shown that people have a comparatively differentiated understanding of what playfulness is: Proyer (2014b) asked 299 participants to name ways to use playfulness and found that people produced between 0 and 27 functions ( M = 6.2, SD = 3.6, median = 6) that could be clustered into seven categories (e.g., wellbeing, mastery orientations, and relationships; see Barabadi et al, 2022 , for a replication). Women reported more functions than men and higher self-reported playfulness related to reporting more functions and greater diversity (i.e., responses covered many of the broader categories).…”
Section: Introductionmentioning
confidence: 99%